Preventing COVID-19 Transmission on Labor and Delivery: A Decision Analysis - Savitsky, Leah M.; Albright, Catherine M. (American Journal of Perinatology, 2020)
Objective The health care system has been struggling to find the optimal way to protect patients and staff from coronavirus disease 2019 (COVID-19). Our objective was to evaluate the impact of two strategies on transmission of COVID-19 to health care workers (HCW) on labor and delivery (L&D).Study Design We developed a decision analytic model comparing universal COVID-19 screening and universal PPE on L&D. Probabilities and costs were derived from the literature. We used individual models to evaluate different scenarios including spontaneous labor, induced labor, and planned cesarean delivery (CD). The primary outcome was the cost to prevent COVID-19 infection in one HCW. A cost-effectiveness threshold was set at $25,000 to prevent a single infection in an HCW.Results In the base case using a COVID-19 prevalence of 0.36% (the rate in the United States at the time), universal screening is the preferred strategy because while universal PPE is more effective at preventing COVID-19 transmission, it is also more costly, costing $4,175,229 and $3,413,251 to prevent one infection in the setting of spontaneous and induced labor, respectively. For planned CD, universal PPE is cost saving. The model is sensitive to variations in the prevalence of COVID-19 and the cost of PPE. Universal PPE becomes cost-effective at a COVID-19 prevalence of 34.3 and 29.5% and at a PPE cost of $512.62 and $463.20 for spontaneous and induced labor, respectively. At a higher cost-effectiveness threshold, the prevalence of COVID-19 can be lower for universal PPE to become cost-effective.Conclusion Universal COVID-19 screening is generally the preferred option. However, in locations with high COVID-19 prevalence or where the local societal cost of one HCW being unavailable is the highest such as in rural areas, universal PPE may be cost-effective and preferred. This model may help to provide guidance regarding allocation of resources on L&D during these current and future pandemics.Key Points
Keywords: cost-effectiveness analysis; COVID-19; decision analysis; personal protective equipment; universal screening